Sexuality and Eschatology: In Search of a Celibate Utopia in Pseudepigraphic Literature - Loader, William R.G. (Journal for the study of the pseudepigrapha, 2014)
This article investigates the possible backgrounds in Jewish pseudepigraphical literature of the notion expressed in Mk 12.25 that the age of resurrection life will be without sexual relations. It identifies the potential for such a view to develop on the basis of presuppositions present in Jubilees of paradise as a temple, then turns to a discussion of depictions of resurrected life in Jewish literature, which normally envisages resurrected life as a transformed state corresponding to present realities and so including both sacred space and other space where marriage and sexual relations belong, often producing abundant progeny. It then considers eschatologies which envisage both an earthly messianic reign and, following it, a more heavenly state, before returning to Mark and related early Christian eschatologies. It concludes that Mk 12.25 most likely reflects notions of resurrected life being in holy space, perhaps linked to ideas of the transformed state as rendering sexual relations also unimportant.